Integrasi Nilai-Nilai Islam dalam Pengambilan Keputusan pada Perencanaan Pendidikan di Sekolah Islam - Rini, Rini; Hidayat, Wahyu; Asmendri, Asmendri; Sari, Milya (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2025)
This study aims to formulate an integrative decision-making model based on Islamic values to improve the quality of Islamic school governance. Through a systematic literature review of publications from 2020 to 2025, this study identifies the gap between modern managerial approaches and the integration of religious values in decision-making practices in Islamic schools. The findings show that the quality of decisions depends on the balance between technical rationality and moral orientation based on the principles of shura, amanah, 'adl, and maslahah. The resulting model includes five stages: preparation and agenda setting, data collection and analysis, deliberation and consensus, value-based implementation, and evaluation and spiritual reflection. Each stage is designed to ensure that technical and value aspects go hand in hand, resulting in inclusive, fair, and maslahah-oriented policies. The study also identified implementation challenges, including weak documentation of deliberations, low data utilization, uneven value leadership capacity, and the dominance of administrative orientation. This integrative model offers a practical framework for Islamic school leaders in formulating policies that are both managerially effective and in line with religious identity, thereby fostering an educational environment that shapes the character and achievements of students holistically